2020
DOI: 10.3390/app10249152
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity and Electrical Impedance Measurement in Mortar and Concrete Elements: A Systematic Review

Abstract: This paper aims at analyzing the state-of-the-art techniques to measure electrical impedance (and, consequently, electrical resistivity) of mortar/concrete elements. Despite the validity of the concept being widely proven in the literature, a clear standard for this measurement is still missing. Different methods are described and discussed, highlighting pros and cons with respect to their performance, reliability, and degree of maturity. Both monitoring and inspection approaches are possible by using electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 185 publications
(364 reference statements)
2
36
0
Order By: Relevance
“…Mainly due to the pozzolanic or latent-hydraulic reaction of SCMs, such as GGBS, silica fume or fly ash the pore structure becomes finer and less permeable, and thus the conductivity of the pore solution is reduced. The same phenomenon can be observed using finer cements, such as cements with higher strength classes (e.g., [ 42 , 46 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]).…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Mainly due to the pozzolanic or latent-hydraulic reaction of SCMs, such as GGBS, silica fume or fly ash the pore structure becomes finer and less permeable, and thus the conductivity of the pore solution is reduced. The same phenomenon can be observed using finer cements, such as cements with higher strength classes (e.g., [ 42 , 46 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]).…”
Section: Introductionmentioning
confidence: 53%
“…As stated in several studies (e.g., [ 11 , 26 , 37 , 38 , 41 , 44 , 45 , 46 , 47 , 48 ]), the increase in porosity, which can be a result of a higher w/c ratio or due to an increased binder content, generally led to a reduced electrical resistivity. However, in contrast to [ 41 , 44 , 45 , 46 , 47 , 48 ], both parameters in this study showed interaction effects.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations